The prolyl isomerase Pin1 orchestrates p53 acetylation and dissociation from the apoptosis inhibitor iASPP. - Mantovani, F; Tocco, F; Girardini, J; Smith, P; Gasco, M; Lu, X; Crook, T; Del Sal, G (2007)
The tumor-suppressor function of p53 relies on its transcriptional activity, which is modulated by post-translational modifications and interactions with regulatory proteins. The prolyl isomerase Pin1 has a central role in transducing phosphorylation of p53 into conformational changes that affect p53 stability and function. We found that Pin1 is required for efficient loading of p53 on target promoters upon stress. In addition, Pin1 is recruited to chromatin by p53 and stimulates binding of the p300 acetyltransferase and consequent p53 acetylation. Accordingly, tumor-associated mutations at Pin1-binding residues within the p53 proline-rich domain hamper acetylation of p53 by p300. After phosphorylation of p53 at Ser46 triggered by cytotoxic stimuli, Pin1 also mediates p53's dissociation from the apoptosis inhibitor iASPP, promoting cell death. In tumors bearing wild-type p53, expression of Pin1 and iASPP are inversely correlated, supporting the clinical relevance of these interactions.